Common fixed points under Lipschitz type condition - Pant, Vyomesh (Kathmandu University Journal of Science Engineering and Technology, 2011)
The present paper is aimed at obtaining common fixed point theorems for a pair of selfmaps satisfying nonexpansive or Lipschitz type condition by using the notion of pointwise R- weak commutativity but without assuming the completeness of the space or continuity of the mappings involved.